Acute myocardial infarction in a patient with anomalous left main coronary artery origin with a hypoplastic left anterior descending artery: A diagnostic and therapeutic challenge - Cremer, M; Patel, A (SA Heart Journal, 2025)
Congenital coronary artery anomalies are rare but clinically significant. We present a 41-year-old Caucasian male who presented with acute ST-elevation myocardial infarction (STEMI) involving two distinct vascular territories. Initial electrocardiogram (ECG) findings showed ST-segment elevation in the inferior and anterolateral leads, raising suspicion of multivessel involvement. Delayed access to a cardiac catheterisation laboratory warranted thrombolysis as the primary reperfusion strategy; however, this was unsuccessful. Emergent coronary angiography revealed an anomalous left main coronary artery (LMCA) originating from the right coronary cusp, sharing a common ostium with the right coronary artery (RCA). A critical stenosis of the mid-RCA was identified, attenuated proximally by a thrombolysis in myocardial infarction (TIMI) 3 thrombus burden and complete occlusion of its distal branches. Coronary computed tomography angiography (CCTA) further revealed a hypoplastic left anterior descending artery (LAD). The patient was initially managed with medical therapy alone, and subsequent percutaneous coronary intervention (PCI) was performed for ongoing stable angina, resulting in complete coronary revascularisation. This case highlights the importance of considering coronary anomalies in patients with atypical clinical presentations and the need for individualised treatment approaches. The coexistence of congenital and atherosclerotic coronary artery disease poses significant challenges, and further studies are needed to refine screening and management guidelines. Keywords: congenital coronary artery anomal, anomalous left main coronary artery origin, anomaly, hypoplastic left anterior descending artery, myocardial infarction, coronary computed tomography angiography